Opportunities for a Low Carbon Transition-Deploying Carbon Capture, Utilization, and Storage in Northeast India - Datta, Aparajita; Krishnamoorti, Ramanan (Frontiers in Energy Research, 2019)
As development in India paces up, energy demand is projected to increase; exerting pressure on the environment and presenting the added challenge of mitigating greenhouse gas emissions at an accelerated pace. Carbon capture, utilization, and sequestration (CCUS) is one of the mitigation strategies that India could adopt in this context, in the backdrop of an energy industry largely dominated by coal. Specifically, the north-eastern state of Assam in India is home to large point sources of CO2 emissions like power, chemical or fertilizer plants, and has abundant sinks in the form of mature oil fields, coal beds, and saline aquifers. This work discusses the emission cuts that can be achieved by retrofitting existing point-sources with CCUS systems, and the techno-economic considerations thereof. We analyze how the levelized cost of electricity will change across three power plants, and how the economics of capture and avoidance costs at a chemical plant can revive its current financial situation, to present why there is an incentive for CCUS in Assam. The results show that for any CCUS implementation plant design, age and preparedness are factors that influence the economics and can lead to huge differentials. Since no new major expansions are planned in the region, investing in retrofitting will deliver immediate results towards achieving climate goals, while allowing time for the future deployment of renewable energy sources and energy storage solutions.